Representation of Ethnicity, Cultural Identity and Marginalized Voices in Nepali Literature - Limbu, Ramesh Kumar (Journal of Nepalese Studies, 2025)
This article critically explores the representation of ethnicity, cultural identity, and marginalized voices in Nepali literature, focusing on how literary texts reflect and negotiate the diverse socio-cultural realities of Nepal. It analyses works by writers from various caste and ethnic communities, highlighting the ways in which language, narrative traditions, and local histories shape literary expression. Special attentions is given to the depiction of Indigenous nationalities, Dalits, women and other underrepresented groups whose experiences have often been overlooked within mainstream literary discourse. Historically dominated by the perspectives of so-called high-caste hill elites, Nepali literature is now witnessing the emergence of narratives that reflect the lived experiences, languages, and traditions of marginalized communities. Drawing on postcolonial, intersectional, and cultural theories, this study analyzes key literary works and scholarly critiques that highlight both the exclusion and resurgence of ethnic and indigenous expression in Nepali literature. The paper argues that contemporary literary voices contribute significantly to redefining national identity by challenging dominant narratives and foregrounding pluralistic understandings of belonging, identity, and social justice in Nepal.